Pengembangan Aplikasi Berbasis Responsive Website Menggunakan Metode Extreme Programming - Dedy Armiady (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The use of information technology, especially computer network-based applications, is currently increasingly widespread. This is indicated by the number of educational institutions that have begun to apply this technology to solve various problems faced. One of the educational institutions currently committed to implementing information technology is the Almuslim Integrated Islamic Boarding School. This study aims to develop an information system for the registration of prospective new students at the Almuslim Integrated Islamic Boarding School based on a responsive website using the Extreme Programming (XP) method. This method is used to achieve the ultimate goal of system development quickly and effectively. Development Based on the system implemented, this method is able to accommodate the system development process quickly with a focus on the process of writing program code. The results obtained are a responsive website-based information system for registration of prospective new students which was developed in a short time. This result is different from the development of the previous system using the waterfall model